The postal age : the emergence of modern communications in nineteenth-century America - Henkin, David M. (University Of Chicago Press, 2006)
Many of us may not realize that what we now call snail mail was once just as revolutionary as e-mail and text messages are today. As David M. Henkin argues in The Postal Age, a burgeoning postal network initiated major cultural shifts during the nineteenth century, laying the foundation for the interconnectedness that now defines our ever-evolving world of telecommunications. This fascinating history traces these shifts from their beginnings in the mid-1800s, when cheaper postage, mass literacy, and migration combined to make the long-established postal service a more integral and viable part.